La représentation de la Nuit dans l’Antiquité grecque : fondements, spécificités, significations - Clara Granger (Bollettino della Società Geografica Italiana, 2019)
The representations and evocations of the night, as a luminary and a divinity, seem to be codified, at least systematized in Greek art. The Night, Nyx, is a goddess which is mostly depicted in opposition to other personifications, such as the Sun or the Moon. The reasons must be search both in iconography and mythology. Moreover, the representations of the Night and the figures opposed to her (but at the same time complementary) are symbolic of a temporal and also geographical frame.